ANALYZING RUNOFF DYNAMICS THROUGH PARAMETERIZING A HYDROLOGICAL MODEL IN A WATERSHED: A CASE STUDY IN UPPER SERAYU BASIN, CENTRAL JAVA PROVINCE, INDONESIA - Adhi Nurul Hadi; Sudibyakto Sudibyakto; Dhruba Shrestha (Indonesian Journal of Geography, 2011)
This research constructed a hydrological model by means of available data,hydrological equations, and GIS program to find out the runoff dynamic on thestudy area. The runoff dynamic was analyzed by describing runoff on different landcover types, figuring the correlation between hydrological component and runoff,calculating the sensitivities of the hydrological components to runoff, andidentifying the response of runoff to possible land cover change. The modelresulted that the highest runoff occurred on built up area and the lowest occurredon cultivation area. Infiltration was also the hydrological component that mostlyinfluenced runoff. Replacing forest, shrub, and plantation by cultivation greatlyreduced runoff up to 49 %. Enlarging forest area increased runoff about 12 %.Based on those findings, the hydrological component having the strongestcorrelation with runoff gave the most influence to runoff change, and enlargingforest area does not always decrease runoff.